Sleep Loss and Affective Functioning: More Than Just Mood. Issue 5 (3rd September 2017) - Watling, Jordan; Pawlik, Bartholomew; Scott, Kelly; Booth, Stephen; Short, Michelle A.
Abstract : Empirical evidence supports an intimate link between sleep and affective functioning. While the bidirectional relationship between sleep duration and mood is well documented, limited research targets other aspects of affective functioning, such as emotion and emotion regulation, or considers their interrelationships. The present review summarizes research examining the relationship between sleep and emotion, emotion regulation, and mood, and presents a theoretical model representing the relationships between these constructs. Disruptions to sleep and mood may trigger and maintain a negative cascade, leading to more entrenched sleep problems and psychopathology. Given that insufficient sleep is a widespread phenomenon, understanding the interrelationships between sleep and affective functioning has implications for both public health and clinical practice.